A raiz da equação é:
![\sqrt[3]{3x + 1 } = \sqrt[3]{ x + 7} \sqrt[3]{3x + 1 } = \sqrt[3]{ x + 7}](https://tex.z-dn.net/?f=+%5Csqrt%5B3%5D%7B3x+%2B+1+%7D++%3D++%5Csqrt%5B3%5D%7B+x+%2B+7%7D+)
(A) S = {- 2}
(B) S = {2}
(C) S = {7}
(D) S = {- 3}
(E) S = {3}
Soluções para a tarefa
Respondido por
0
Resposta:
Desculpas eu não sei
Explicação passo-a-passo:
Só respondi pra me consegui acessar o aplicativo
Perguntas interessantes
Biologia,
7 meses atrás
Matemática,
7 meses atrás
Inglês,
7 meses atrás
Matemática,
8 meses atrás
Português,
8 meses atrás
Ed. Física,
1 ano atrás
Geografia,
1 ano atrás